Association between hypervolemia and ventricular hypertrophy in hemodialysis patients - Martin, Luis Cuadrado [UNESP]; Franco, U. S.; Gavras, I; Matsubara, Beatriz Bojikian [UNESP]; Garcia, S.; Caramori, I; Barretti, B. B.; Balbi, André Luis [UNESP]; Barsanti, R.; Padovani, C.; Gavras, H. (Elsevier B.V., 2004)
Background: Left ventricular hypertrophy (LVH) is a well-known predictor of cardiovascular mortality in patients who have end-stage renal disease and are maintained on hemodialysis (HD), and LVH is not always correlated with the severity of hypertension in these patients. The purpose of this study was to investigate the role of other factors contributing to LVH.Methods: A total of 50 patients with HD were classified in three groups according to whether their LV mass index (LVMI) was higher than (n = 15), equal to (n = 20), or lower than (n = 15) that predicted by a formula based on their ambulatory blood pressure monitoring (ABPM).Results: Subjects with higher LVMI than predicted had significantly greater inter-HD weight gain (3.4 +/- 0.8 v 2.7 +/- 0.8 and 2.6 +/- 05 kg, respectively, in the other two groups, P < .05), and subjects with lower LVMI than predicted had a tendency toward a more pronounced nocturnal dipping pattern of BP (P = .07 v the other two groups), although daytime and night-time average BP levels did not differ between groups. All other clinical and laboratory parameters were similar among the three groups except higher cardiac output and various indices of LVH, which were more pronounced in the group with higher LVMI by ABPM. This group had also the lowest survival rate over the 2 to 3 years of follow-up, with five deaths versus two in each of the other two groups.Conclusions: the data suggest that correct management of inter-HD weight gain by nutritional counseling and shorter inter-HD intervals may prevent LVH and improve survival independently of BP control. (C) 2004 American Journal of Hypertension, Ltd.
Keywords: interdialytic weight gain; left ventricular mass; ambulatory blood pressure monitoring; cardiovascular mortality